Compositional Optimization of Emission Properties for Rare-Earth Doped Fluoride Phosphate Glasses: Structural Investigations via NMR, EPR, and Optical Spectroscopies - Galleani, Gustavo; Doerenkamp, Carsten; Santagneli, Silvia [UNESP]; Magon, Claudio Jose; Camargo, Andrea S. S. de; Eckert, Hellmut (Amer Chemical Soc, 2019)
A detailed structural investigation of two series of fluoride phosphate glasses with nominal compositions 20BaF(2)-20SrF(2)-20ZnF(2)-xIn(PO3)(3)-(40 - x)InF3 (x = 0, 5, 10, and 15) and 20BaF(2)-20SrF(2)-20ZnF(2)-10ScF(3)-xIn(PO3)(3)-(30 - x)InF3 (x = 0, 10, 15, 20), both doped with either 0.2 mol % Yb3+ or 0.S mol % Eu3+, has been conducted. As indicated by Raman scattering and solid- state NMR, the network structure is dominated by six-coordinated In3+, orthophosphate Q((0)()) species, and the (near) absence of P-O-P connectivity. The ligand environment of the rare-earth ions is studied by (1) Sc-45 NMR of the diamagnetic mimic Sc3+, (2) echo-detected field-sweep EPR spectra at the X-band, using Yb3+ spin probes, and (3) excitation and emission spectroscopy of Eu3+ dopants. Sc-45{P-31} rotational echo double resonance (REDOR) results, the ratio of the Eu3+ D-5(0) -> F-7(2) to (5) D-0 -> F-7(1) emission intensities, the lifetime values of the Eu3+ emitting level D-5(0), as well as the g factor measured by EPR spectroscopy consistently indicate that the fluoride ligands strongly dominate in the first coordination sphere of the rare-earth ions. This result stands in contrast to previous studies on aluminofluorophosphate glasses with similar compositions that show mixed ligation of the rare-earth ions by fluoride and phosphate ions. Thus, by substituting aluminum by its homologue indium one can achieve the original design goal of fluoride phosphate glasses, which is the creation of a framework structure dominated by oxide, while the local environment of the RE emitting ion is dominated by fluoride ligands, so as to improve their emissive properties. The results also illustrate the successful use of the previously developed combined NMR/EPR/optical characterization strategy for the design of optimized matrices for rare-earth ion emitters.